2016
DOI: 10.17795/jjnpp-25814
|View full text |Cite
|
Sign up to set email alerts
|

Ficus carica Leaves Decoction on Glycemic Factors of Patients With Type 2 Diabetes Mellitus: A Double-Blind Clinical Trial

Abstract: Background: It is advisable to pay sufficient heed to the high prevalence of diabetes mellitus (DM) management, which has heavy burden and remarkable impact on the patients' life quality. Objectives: The current study aimed to evaluate hypoglycemic effects of Ficus carica (FC) decoction (common fig leaf) in patients with type 2 DM. Patients and Methods: It was a double-blind cross-over clinical trial. There were two groups of 14 subjects. During the first phase of the study, one group received fig leaf decocti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Bio-efficacy testing in humans shows the decoction of leaves effectively controlled postprandial glycemia in individuals with T1DM (type 1 diabetes mellitus) [102]. Furthermore, a study by Mazhin et al (2016) showed that the addition of a fig leaf decoction, compared to oral hypoglycemic drugs, significantly decreased 2 h postprandial glycemia in patients with T2DM (type 2 diabetes mellitus) [103]. In another study, the effect of fig was compared with the oral drug metformin in people with T2DM [104] and this showed that metformin decreased blood sugar levels by 27.6% and figs decreased blood sugar levels by 13.5% after 2 months of treatment.…”
Section: Diabetes Benefitsmentioning
confidence: 99%
“…Bio-efficacy testing in humans shows the decoction of leaves effectively controlled postprandial glycemia in individuals with T1DM (type 1 diabetes mellitus) [102]. Furthermore, a study by Mazhin et al (2016) showed that the addition of a fig leaf decoction, compared to oral hypoglycemic drugs, significantly decreased 2 h postprandial glycemia in patients with T2DM (type 2 diabetes mellitus) [103]. In another study, the effect of fig was compared with the oral drug metformin in people with T2DM [104] and this showed that metformin decreased blood sugar levels by 27.6% and figs decreased blood sugar levels by 13.5% after 2 months of treatment.…”
Section: Diabetes Benefitsmentioning
confidence: 99%